The induced knockdown of GmCAD receptor protein encoding gene in Galleria mellonella decreased the insect susceptibility to a Photorhabdus akhurstii oral toxin. Issue 1 (31st December 2021) - Dutta, Tushar K.; Veeresh, Arudhimath; Mathur, Chetna; Phani, Victor; Mandal, Abhishek; Sagar, Doddachowdappa; Nebapure, Suresh M.
ABSTRACT: Photorhabdus bacteria secrete a repertoire of protein toxins that can kill the host insect. Among them, toxin complex (Tc) proteins have gained significant attention due to their wider conservation across the different bacterial genera. In our laboratory, a C-terminal domain of TcaB protein was characterized from P. akhurstii bacterium that conferred the potent oral insecticidal effect on Galleria mellonella . However, the role of insect gut receptors in the TcaB intoxication process was yet to be investigated. In the current study, we examined the transcription of candidate midgut receptors in TcaB-infected larvae and subsequently cloned a cadherin-like gene, GmCAD, from G. mellonella. GmCAD was highly transcribed in the fourth-instar larval stage and specifically in the midgut tissues. Our ligand blot and binding ELISA assays indicated that TcaB binds to the truncated peptides from the GmCAD transmembrane-proximal region with greater affinity than that from the transmembrane-distal region. Oral administration of bacterially expressed GmCAD dsRNA in G. mellonella severely attenuated the expression of target mRNA, which in turn alleviated the negative effect of TcaB on insect survival (TcaB-induced mortality in CAD dsRNA pretreated larvae reduced by 72–83% compared to control), implying the association of GmCAD in the TcaB intoxication process. Present findings form a basis of future research related to the insect gut receptor interactions with Photorhabdus toxins.